Peramalan Jumlah Pengunjung Objek Wisata Gumul Paradise Island Kabupaten Kediri Menggunakan Metode Prophet - Yudha Alif Auliya; Yanuar Nurdiansyah; Ari Puji Astuti (INFORMAL: Informatics Journal, 2023)
The obstacle most often faced by tourist attractions is related to the variable number of visitors where the number of visitors has decreased due to the co-19 pandemic. This variable number of visitors can be an obstacle for tourist attraction managers to be able to maximize the income earned. This study aims to develop a forecasting system for the number of visitors to Gumul Paradise Island by applying the Prophet Method. The stages of the research include communication, prophet modeling, and evaluation of results. The data used as training data is visitor data from 2012 to 2021. This study used data-filling techniques to fill in the blank training data. The accuracy rate of forecasting the number of visitors is 99.387% in comparing the forecasting results of training data with test data and 90.242% in forecasting results with actual data. This can be interpreted that the forecasting model using the prophet method can predict the number of visitors to the Gumul Paradise Island tourist attraction.